Educational Personnel Administration - Fatimah, Meti; Ikhsanuddin, Muhammad; Kholil; Hidayat , Muhtar (UNIVERSITAS SERAMBI MEKKAH, 2024)
Educational personnel administration is the entire process of activities that are planned and carried out deliberately and seriously as well as providing ongoing and ongoing guidance to teachers and employees in schools or educational institutions. Personnel administration is the entire structuring process that is concerned with the problem of obtaining and using the workforce and the school efficiently, in order to achieve predetermined school goals. With good administration of teachers and employees, we can achieve our business goals even better, namely more effectively and more efficiently. This administration is a tool to achieve goals faster, more successfully, more economically in the use of tools and costs. In personnel administration, it is the main supporting element that enables students to excel in the teaching and learning process. Among personnel members there are arrangements of duties and responsibilities.